Performance of Sudanese Desert Lambs Fed Graded Levels of Roselle (Hibiscus sabdariffa) Seeds Instead of Groundnut Cake - Beshir, Amani A.; Babiker, Salih Ahmed (Pakistan Journal of Nutrition, 2009)
The present study was conducted to evaluate roselle (Hibiscus sabdariffa) seed cake as a possible protein supplement for growing Iamb in comparison to groundnut cake. Graded proportion of roselle seed (RS) (0, 10, 20%) which replace Groundnut Cake (GNC) were incorporated in three diets iso-caloric, iso-nitrogenous diets for lambs. Diet A contained 0% Roselle seed while diets B and C obtained 10 and 20% roselle seed respectively. Thirty yearling male lambs of Sudan desert sheep ecotype Kabashi with average body weight of 25.2 kg were used for feeding trial. There was a significant (p<0.05) linear increase in feed intake with increasing RS level in the diet, but dietary treatments had no significant effect on average daily gain, feed conversion efficiency and final body weight. In spite of that lambs fed diets containing roselle seed were found to be superior over the control group in the previous parameters.